Patient satisfaction concerning assisted reproductive technology treatments in moderate to severe endometriosis. (November 2014) - van der Houwen, Lisette E.E.; Schreurs, Anneke M.F.; Schats, Roel; Lambalk, Cornelis B.; Hompes, Peter G.A.; Mijatovic, Velja
Abstract A prospective observational cohort study was performed to examine patient satisfaction after one Assisted Reproductive Technology (ART) treatment cycle in moderate to severe endometriosis patients. From May 2012 till September 2013, 25 patients with surgically proven endometriosis stage III-IV were included per group and received intrauterine insemination (IUI), in vitro fertilization (IVF) or IVF preceded by long-term pituitary down-regulation (IVF-ultralong). The median patient satisfaction scores were 8.3, 7.9 and 8.0 in patients receiving IUI (n = 22), IVF (n = 24) and IVF-ultralong (n = 23), respectively (p = 0.89). Both deterioration in pain and quality-of-life could not be identified as determinants of decreased patient satisfaction scores. Satisfaction was higher in women receiving their first ART treatment attempt (p = 0.002), after treatment accomplishment (p = 0.04) and after a positive pregnancy test (p = 0.04). A median satisfaction score concerning preceding long term pituitary down-regulation of 6.1 (IVF-ultralong n = 25, IUI n = 8) was reported. Only three patients would refrain from this preceding therapy in a next treatment attempt. We concluded that patient satisfaction scores were comparable between the three different ART treatments. Since patient satisfaction was in particular dependent on treatment outcomes, it is recommended to compare those three ART treatments in a randomized controlled trial investigating the efficacy, safety and cost-effectiveness.